Comparative Pathogenesis of Generalist AcMNPV and Specific RanuNPV in Larvae of Rachiplusia nu (Lepidoptera: Noctuidae) Following Single and Mixed Inoculations - Decker Franco, Cecilia; Taibo, Catalina Beatriz; Di Rienzo, Julio A.; Alfonso, Victoria; Arneodo Larochette, Joel Demian (Oxford University Press, 2021)
The South American soybean pest, Rachiplusia nu (Guenée), is naturally infected by Autographa californica multiple nucleopolyhedrovirus (AcMNPV) and Rachiplusia nu nucleopolyhedrovirus (RanuNPV). We compared their pathogenicity to fourth-instar R. nu larvae, by evaluating time to death and virus spread throughout the tissues in single and mixed infections. Bioassays showed that generalist AcMNPV had a faster speed of kill than specific RanuNPV, while the mixed-virus treatment did not statistically differ from AcMNPV alone. Histopathology evidenced similar tissue tropism for both viruses, but co-inoculation resulted in mostly AcMNPV-infected cells. In sequential inoculations, however, the first virus administered predominated over the second one. Implications on baculovirus interactions and biocontrol potential are discussed.